MANAJEMEN PENGELOLAAN KONFLIK DI SEKOLAH - Yusra Jamali (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
Conflict does not always have to be perceived by destroying or destroying a school. Considerably that the presence of conflict in schools is destructive and that there is a new power for school change and for the people in it. The method of determining whether a conflict can be destructive or constructive can be done through an in-depth analysis study, knowing in advance what the cause of the conflict is, what is the motive of the conflict, why the conflict can occur. From various studies, school conflicts are caused by non-transparent headmasters in financial reporting, arrogant to teachers, students and staff; Make policy at will; Do wild pengutan, and teachers do violence against students during the hours of lessons take place. Conflict can build a school from its non-development, that is, school personnel encourage the conflict to be presented so that leaders can realize that at school there must be a change in leadership management.